The effect of social networks on academic self-handicapping with the mediating role of self-regulatory learning strategies and academic achievement among EFL students - Izadpanah, Siros; Charmi, Mahdis (Frontiers in Psychology, 2022)
In the academic context, social networking sites (SNSs) have reshaped the way university students connect and communicate with each other and the way they learn, thus influencing their identities and dimensions. This research aims to investigate the effect of social networks on academic self-handicapping with the mediating role of self-regulatory and academic achievement. The current study is considered to be quantitative research in terms of its nature, applied research in terms of its purpose, and correlational descriptive one in terms of its method. The statistical population of the present study includes all language students of Tabriz University, whose number was 540 people. Sampling was done by the random sampling method. Using Morgan’s table, the sample size was estimated to be 225 people in 2022. Due to the possibility of falling, 10% was added to this number and 250 questionnaires were distributed among 250 participants, 17 questionnaires were incomplete and a total of 233 proper questionnaires were examined. Four questionnaires were administered to collect data: Social networking by Sadeghi Amin (2017), Jones and Rodwalt’s (1982) self-handicapping questionnaire, self-regulatory learning strategies questionnaire by Pintrich and DeGroot (2000), and academic achievement by Pham and Taylor (1994) standard questionnaire. SPSS 26 and AMOS 24 software were used to analyze the collected data from questionnaires. Descriptive, inferential, and Structural Covariance Matrix (SEM) statistics were conducted to explore the effect of social networks on these variables. Findings showed that social networks have a significant effect on self-handicapping in language students of Tabriz University. 2- Social networks have a significant effect on self- self-handicapping with a mediating role of self-regulation learning strategies in language students of Tabriz University. 3- Social networks have a significant effect on self-handicapping with a mediating role of academic progress in language students of Tabriz University. These findings might be useful for language teachers, instructors, and syllabus designers.